Tap channel castable based on novel carbon source and preparation method of tap channel castable
By modifying the scale graphite to prepare a new carbon source and combining other components for the preparation of iron groove castable, the existing carbon sources are solved by solving the problem of flammable, volatile or oxidized at high temperatures, significantly improving the performance and service life of the material.
Patent Information
- Application Number
- CN202411951484.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-25
AI Technical Summary
The existing carbon sources in iron-out castables, such as ball asphalt, graphite, etc., are prone to combustion, volatilization or oxidation at high temperatures, resulting in a shortening of the service life of the material and difficulty in dispersing evenly, affecting the performance of the material.
By surface treatment of scale graphite and high-temperature in situ reaction, a new carbon source was prepared and used in the preparation of iron groove castable, combining other ingredients such as electromelted brown corundum, silicon carbide, α-alumina powder, etc. to form an optimized formula.
The new carbon source significantly improves the flexural strength, compressive strength and thermal shock stability of the castable material at room temperature, extends the service life of the material, reduces the amount of water added, and improves the dispersion performance of the material.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of refractory materials, and in particular relates to a tapping trough castable based on a novel carbon source and a preparation method thereof. Background Art
[0002] The refractory material for the iron ditch generally uses Al2O3-SiC-C castable, which is a castable with alumina, silicon carbide and carbon as the main components. Among them, carbon materials have high thermal conductivity, which can improve the thermal shock stability of the material, prevent the penetration of slag into the interior of the material, improve the corrosion resistance of the material, and thus extend the service performance of the blast furnace iron ditch. Therefore, in the preparation process of castables, carbon materials are indispensable raw materials. Among traditional castables, ball asphalt is often used as the main carbon source for iron ditch castables due to its spherical shape, good hydrophilicity and low cost. However, asphalt is easy to burn and volatilize at high temperatures, and produces harmful gases. In addition, the residual carbon rate is low and it is easy to oxidize, which affects the service life of the castable. Therefore, it is often necessary to add antioxidants.
[0003] Carbon black has a fine particle size (average particle size is 280 nm) and is widely used in iron trough castables to improve corrosion resistance due to its good filling performance. However, its high specific surface area is not conducive to its dispersion in the castable, resulting in an increase in the amount of water required for the castable, which deteriorates the performance of the castable.
[0004] In addition, graphite is another carbon source for the iron ditch castable. Graphite has a layered structure, which is why graphite is anisotropic. Due to its unique structure, graphite can be used to improve thermal shock resistance and slag erosion resistance. However, graphite has poor hydrophilicity, and is prone to floating and agglomeration in the castable, making it difficult to disperse evenly, which increases the water demand and degrades the performance of the castable. At the same time, in a high-temperature oxidizing atmosphere, graphite is easily oxidized and forms pores, which increases the porosity of the refractory material, thereby reducing the slag resistance and mechanical properties of the refractory material. These problems hinder the application of flake graphite in castables. Therefore, the present invention modifies flake graphite to form a new carbon source, and applies it to the iron ditch castable to improve the performance and life of the castable. Summary of the invention
[0005] The first purpose of the present invention is to provide a tapping trough castable based on a novel carbon source, and to improve the performance of the castable by modifying the carbon source.
[0006] The second purpose of the present invention is to provide a method for preparing a tapping trough castable based on a novel carbon source, which method is simple and can be mass-produced.
[0007] In order to solve the above problems, the technical solution adopted by the present invention is as follows:
[0008] A tapping trough castable based on a novel carbon source, wherein the components are composed as follows by weight: 45-60 parts of fused brown corundum, 12-18 parts of silicon carbide, 2-5 parts of a novel carbon source, 8-12 parts of dense corundum, 4-8 parts of α-alumina micropowder, 2-6 parts of silicon micropowder, 3-6 parts of calcium aluminate cement, 0.2-0.6 parts of metallic silicon powder, 0.05-0.3 parts of metallic aluminum powder, and 0.05-0.2 parts of a dispersant.
[0009] Furthermore, the composition of each component is as follows, measured by weight: 45-55 parts of fused brown corundum, 12-16 parts of silicon carbide, 2-3 parts of new carbon source, 8-11 parts of dense corundum, 4-6 parts of α-alumina micropowder, 2-4 parts of silicon micropowder, 3-5 parts of calcium aluminate cement, 0.5-0.6 parts of metallic silicon powder, 0.05-0.1 parts of metallic aluminum powder, and 0.1-0.2 parts of dispersant.
[0010] Furthermore, in terms of weight, the components are as follows: 55 parts of fused brown corundum, 16 parts of silicon carbide, 3 parts of new carbon source, 11 parts of dense corundum, 6 parts of α-alumina micropowder, 4 parts of silicon micropowder, 5 parts of calcium aluminate cement, 0.5 parts of metallic silicon powder, 0.1 parts of metallic aluminum powder, and 0.1 parts of dispersant.
[0011] Furthermore, the particle size range of the fused brown corundum is 1-12 mm, and the content of Al2O3 in the fused brown corundum is ≥96 wt.%.
[0012] Furthermore, the particle size of the silicon carbide does not exceed 3 mm, and the SiC content is ≥ 97 wt.%.
[0013] Furthermore, the preparation method of the novel carbon source is: surface treating flake graphite to obtain a mixture; adding metal silicon powder and metal zirconium powder to the mixture, mixing by ball milling, and then utilizing high temperature in-situ reaction to obtain the novel carbon source.
[0014] Furthermore, the particle size of the α-alumina micropowder does not exceed 0.0374 mm, and the content of Al2O3 in the α-alumina micropowder is ≥99 wt.%.
[0015] Furthermore, the binder is calcium aluminate cement with an Al2O3 content of ≥68.5 wt.%, and a CaO content of ≤31 wt.%.
[0016] Furthermore, the dispersant is a mixture of polycarboxylate FS20 and sodium hexametaphosphate.
[0017] Furthermore, the method for preparing any of the above-mentioned tapping channel castables based on the novel carbon source comprises the following steps:
[0018] (1) Weigh all the raw materials according to the formula into a blender, mix them initially, then add deionized water and stir evenly;
[0019] (2) After being stirred evenly, pour the casting material into the mold and cast it on a vibration table to obtain a test bar;
[0020] (3) The sample is demolded, cured, dried and heat treated to obtain a trough castable containing a new carbon source.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] (1) The novel carbon source used in the present invention is an environmentally friendly carbon source with a higher residual carbon rate. Compared with traditional carbon sources, such as spherical pitch and graphite, it can avoid the generation of harmful gases during the baking process and improve the working environment in front of the furnace.
[0023] (2) The novel carbon source of the present invention overcomes the defects of ordinary flake graphite in terms of poor hydrophilicity and dispersibility. During use, it can reduce the amount of water added to the castable and can also be evenly dispersed in the matrix.
[0024] (3) After the sample of the iron ditch castable containing the new carbon source prepared by the present invention was treated at 1500℃ for 3h, the room temperature flexural strength and room temperature compressive strength increased by at least 15%; after 5 thermal shocks (△T≈1100℃, water cooling), the flexural strength retention rate of the sample increased by at least 20%. After being treated at 1500℃ for 3h, the sample's resistance to slag erosion and anti-oxidation properties were also significantly improved. DETAILED DESCRIPTION
[0025] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with specific embodiments.
[0026] Unless otherwise specified, the materials or reagents used in the following examples are commercially available products.
[0027] Among them, the particle size of fused brown corundum is 1~12mm, and the content of Al2O3 is ≥96 wt.%;
[0028] The particle size of silicon carbide is ≤3mm, and the SiC content is ≥97wt.%;
[0029] The particle size of dense corundum is ≤1mm, and the Al2O3 content is ≥98wt.%;
[0030] The particle size of α-alumina powder is ≤0.0374mm, and the content of Al2O3 in α-Al2O3 powder is ≥99 wt.%
[0031] Silica powder particle size ≤ 0.3 μm, SiO2 content ≥ 95 wt.%;
[0032] The binder is calcium aluminate cement having an Al2O3 content of ≥68.5 wt.%, and a CaO content of ≤31 wt.%;
[0033] The Si content of metallic silicon is ≥98wt%, and the particle size is ≤400 mesh;
[0034] The particle size of aluminum powder is ≤325 mesh;
[0035] The dispersant is a mixture of polycarboxylate FS20 and sodium hexametaphosphate, wherein the mass ratio of FS20 to sodium hexametaphosphate is 1:1.
[0036] The following embodiments disclose a new type of carbon source-based iron trough castable, in which the components are composed as follows by weight: 45-60 parts of fused brown corundum, 12-18 parts of silicon carbide, 2-5 parts of new carbon source, 8-12 parts of dense corundum, 4-8 parts of α-alumina micropowder, 2-6 parts of silicon micropowder, 3-6 parts of calcium aluminate cement, 0.2-0.6 parts of metallic silicon powder, 0.05-0.3 parts of metallic aluminum powder, and 0.05-0.2 parts of dispersant.
[0037] The preparation method of the novel carbon source comprises the following steps:
[0038] Step 1: Add 1.5% of the total weight of a surfactant and 0.8% of the total weight of a silane coupling agent KH-560 to flake graphite with a particle size of 200-325 meshes, continue stirring for 30-45 minutes, obtain a mixture and dry it in an oven at 70°C;
[0039] Step 2: Add the dried mixture from step 1, metal silicon powder and metal zirconium powder in a mass ratio of 3.5:0.45:1.2 into a ball mill and mix them in a planetary ball mill (the speed is set at 350 r / min) to obtain a mixed powder;
[0040] Step 3: Place the mixed powder obtained in step (2) into a tube furnace under an inert atmosphere, heat it to 1350-1400°C at a heating rate of 150°C / min, and keep it at that temperature for 2-3 hours to obtain a new carbon source.
[0041] The test methods used in the following examples or comparative examples are as follows:
[0042] The room temperature flexural strength test is carried out according to GB / T 3001-2017 and GB / T 5072-2018;
[0043] The room temperature compressive strength test is carried out according to GB / T 3001-2017 and GB / T 5072-2018;
[0044] Oxidation resistance: The oxidation corrosion index is the ratio of the area of the non-carbon-enriched area to the initial cross-sectional area of the castable sample. The larger the ratio, the more serious the oxidation.
[0045] Slag erosion resistance: The slag erosion index is the ratio of the slag erosion area of the crucible hole to the initial area of the crucible hole in the cross section of the static slag resistance sample. The larger the ratio, the more serious the slag erosion.
[0046] Thermal shock stability: will be 1500 o The castable sample after sintering at C × 3 h was placed in 1100 o C high temperature electric furnace for 30 min, then take out the sample and water cool it for 5 min, and repeat this cycle 5 times. The thermal shock flexural strength retention rate is the ratio of the flexural strength of the sample after thermal shock to the flexural strength of the sample after sintering at 1500℃ for 3h.
[0047] Example 1
[0048] A trough castable based on a new carbon source, wherein the components are composed as follows by weight: 55 parts of fused brown corundum, 16 parts of silicon carbide, 3 parts of a new carbon source, 11 parts of dense corundum, 6 parts of α-alumina micropowder, 4 parts of silicon micropowder, 5 parts of calcium aluminate cement, 0.5 parts of metallic silicon powder, 0.1 parts of metallic aluminum powder, and 0.1 parts of a dispersant.
[0049] The preparation method of the above-mentioned iron trough castable based on the novel carbon source is as follows:
[0050] According to the above formula, each component raw material is weighed and mixed evenly in a blender, and then deionized water accounting for 4.2% of the total mass of the solid matter is added for stirring; after stirring evenly, the castable is poured into a mold, and cast on a vibration table to obtain a test bar; then the sample is demolded, cured, dried and heat treated (1200℃×3h) to obtain an iron trough castable containing a new carbon source.
[0051] Example 2
[0052] A trough castable based on a new carbon source, wherein the components are composed as follows by weight: 50 parts of fused brown corundum, 14 parts of silicon carbide, 4 parts of a new carbon source, 10 parts of dense corundum, 5 parts of α-alumina micropowder, 5 parts of silicon micropowder, 6 parts of calcium aluminate cement, 0.3 parts of metallic silicon powder, 0.05 parts of metallic aluminum powder, and 0.15 parts of a dispersant.
[0053] The preparation method of the above-mentioned new carbon source iron trough castable is the same as that in Example 1.
[0054] Example 3
[0055] A trough castable based on a new carbon source, wherein the components are composed as follows by weight: 60 parts of fused brown corundum, 18 parts of silicon carbide, 2 parts of a new carbon source, 8 parts of dense corundum, 4 parts of α-alumina micropowder, 6 parts of silicon micropowder, 3 parts of calcium aluminate cement, 0.6 parts of metallic silicon powder, 0.3 parts of metallic aluminum powder, and 0.2 parts of a dispersant.
[0056] The preparation method of the above-mentioned new carbon source iron trough castable is the same as that in Example 1.
[0057] Example 4
[0058] A trough castable based on a new carbon source, wherein the components are composed as follows by weight: 45 parts of fused brown corundum, 15 parts of silicon carbide, 5 parts of a new carbon source, 12 parts of dense corundum, 8 parts of α-alumina micropowder, 3 parts of silicon micropowder, 4 parts of calcium aluminate cement, 0.4 parts of metallic silicon powder, 0.2 parts of metallic aluminum powder, and 0.05 parts of a dispersant.
[0059] The preparation method of the above-mentioned new carbon source iron trough castable is the same as that in Example 1.
[0060] Example 5
[0061] A trough castable based on a new carbon source, wherein the components are composed as follows by weight: 55 parts of fused brown corundum, 12 parts of silicon carbide, 5 parts of a new carbon source, 12 parts of dense corundum, 7 parts of α-alumina micropowder, 2 parts of silicon micropowder, 5 parts of calcium aluminate cement, 0.2 parts of metallic silicon powder, 0.15 parts of metallic aluminum powder, and 0.1 parts of a dispersant.
[0062] The preparation method of the above-mentioned new carbon source iron trough castable is the same as that in Example 1.
[0063] Example 6
[0064] A trough castable based on a new carbon source, wherein the components are composed as follows by weight: 53 parts of fused brown corundum, 16 parts of silicon carbide, 5 parts of a new carbon source, 9 parts of dense corundum, 6 parts of α-alumina micropowder, 4 parts of silicon micropowder, 6 parts of calcium aluminate cement, 0.6 parts of metallic silicon powder, 0.25 parts of metallic aluminum powder, and 0.1 parts of a dispersant.
[0065] The preparation method of the above-mentioned new carbon source iron trough castable is the same as that in Example 1.
[0066] Comparative Example 1
[0067] A trough castable, wherein the components are as follows in parts by weight:
[0068] Conventional ball asphalt with a particle size of 1-0 mm was used as the carbon source, and the other components were the same as those in Example 1.
[0069] The preparation method of the above-mentioned iron ditch castable is as follows: weigh the raw materials of each component according to the above-mentioned formula, mix them evenly in a mixer, and then add silica sol to stir; after stirring evenly, pour the stirred castable into a mold, and cast it on a vibration table to obtain a test bar; then demold, cure, dry and heat-treat the sample to obtain a cement-free castable for the iron ditch combined with silica sol.
[0070] Comparative Example 2
[0071] A trough castable, wherein the components are as follows in parts by weight:
[0072] Graphite with a mesh size of 200 to 325 was used as the carbon source, and the other components were the same as those in Example 1.
[0073] The preparation method of the above-mentioned iron ditch castable is as follows: weigh the raw materials of each component according to the above-mentioned formula, mix them evenly in a mixer, and then add silica sol to stir; after stirring evenly, pour the stirred castable into a mold, and cast it on a vibration table to obtain a test bar; then demold, cure, dry and heat-treat the sample to obtain a cement-free castable for the iron ditch combined with silica sol.
[0074] The castables prepared in the above Examples 1-6 and Comparative Examples 1-2 were respectively subjected to the following tests: room temperature flexural strength test, room temperature compressive strength test, oxidation resistance test and corrosion resistance test after heat treatment at 1500°C for 3h. The results are shown in Table 1 below.
[0075] Table 1 Test results of castable properties of Examples 1 to 6 and Comparative Examples 1 to 2
[0076]
[0077] As can be seen from Table 1, compared with the castable samples using traditional carbon sources, the room-temperature flexural strength and room-temperature compressive strength of the castable samples containing the new carbon source prepared by the present invention are increased by more than 15% after being treated at 1500°C for 3 hours; the flexural strength retention rate of the sample after 5 thermal shocks (△T≈1100°C, water cooling) is increased by 20%. After being treated at 1500°C for 3 hours, the slag erosion resistance and oxidation resistance of the sample are also significantly improved. The present invention utilizes surface modification technology to improve the water wettability of flake graphite by adding surfactants and silane coupling agents; the new carbon source obtained by high-temperature in-situ reaction of the preliminarily modified graphite with zirconium oxide, etc., can significantly improve the thermal shock stability and slag erosion resistance of the material by improving the bonding mode between the surface coating and the graphite matrix, greatly reduce the cracking and peeling of the material at high temperature, and extend the service life of the castable.
[0078] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A tapping trough castable based on a novel carbon source, characterized in that: In terms of weight, the components are as follows: 45-60 parts of fused brown corundum, 12-18 parts of silicon carbide, 2-5 parts of new carbon source, 8-12 parts of dense corundum, 4-8 parts of α-alumina micropowder, 2-6 parts of silicon micropowder, 3-6 parts of calcium aluminate cement, 0.2-0.6 parts of metallic silicon powder, 0.05-0.3 parts of metallic aluminum powder, and 0.05-0.2 parts of dispersant.
2. The iron trough castable based on the novel carbon source according to claim 1, characterized in that: In terms of weight, the components are as follows: 45-55 parts of fused brown corundum, 12-16 parts of silicon carbide, 2-3 parts of new carbon source, 8-11 parts of dense corundum, 4-6 parts of α-alumina micropowder, 2-4 parts of silicon micropowder, 3-5 parts of calcium aluminate cement, 0.5-0.6 parts of metallic silicon powder, 0.05-0.1 parts of metallic aluminum powder, and 0.1-0.2 parts of dispersant.
3. The iron trough castable based on the novel carbon source according to claim 2, characterized in that: In terms of weight, the components are as follows: 55 parts of fused brown corundum, 16 parts of silicon carbide, 3 parts of new carbon source, 11 parts of dense corundum, 6 parts of α-alumina micropowder, 4 parts of silicon micropowder, 5 parts of calcium aluminate cement, 0.5 parts of metallic silicon powder, 0.1 parts of metallic aluminum powder, and 0.1 parts of dispersant.
4. The iron trough castable based on a novel carbon source according to claim 1, characterized in that: The particle size range of the fused brown corundum is 1-12 mm, and the content of Al2O3 in the fused brown corundum is ≥96 wt.%.
5. The iron trough castable based on a novel carbon source according to claim 1, characterized in that: The particle size of the silicon carbide does not exceed 3 mm, and the SiC content is ≥ 97 wt.%.
6. The iron trough castable based on a novel carbon source according to claim 1, characterized in that: The preparation method of the novel carbon source comprises: performing surface treatment on flake graphite to obtain a mixture; adding metal silicon powder and metal zirconium powder to the mixture, mixing by ball milling, and then utilizing high temperature in-situ reaction to obtain the novel carbon source.
7. The iron trough castable based on a novel carbon source according to claim 1, characterized in that: The particle size of the α-alumina micropowder does not exceed 0.0374 mm, and the content of Al2O3 in the α-alumina micropowder is ≥99 wt.%.
8. The iron trough castable based on a novel carbon source according to claim 1, characterized in that: The binder is calcium aluminate cement with an Al2O3 content of ≥68.5 wt.% and a CaO content of ≤31 wt.%.
9. The iron trough castable based on a novel carbon source according to claim 1, characterized in that: The dispersant is a mixture of polycarboxylate FS20 and sodium hexametaphosphate.
10. A method for preparing a tapping trough castable based on a novel carbon source as claimed in any one of claims 1 to 9, characterized in that: The following steps are involved: (1) Weigh all the raw materials according to the formula into a blender, mix them initially, then add deionized water and stir evenly; (2) After being stirred evenly, pour the casting material into the mold and cast it on a vibration table to obtain a test bar; (3) The sample is demolded, cured, dried and heat treated to obtain a trough castable containing a new carbon source.